If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 32 = 2x + 14 Reorder the terms: 32 + 5x = 2x + 14 Reorder the terms: 32 + 5x = 14 + 2x Solving 32 + 5x = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 32 + 5x + -2x = 14 + 2x + -2x Combine like terms: 5x + -2x = 3x 32 + 3x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 32 + 3x = 14 + 0 32 + 3x = 14 Add '-32' to each side of the equation. 32 + -32 + 3x = 14 + -32 Combine like terms: 32 + -32 = 0 0 + 3x = 14 + -32 3x = 14 + -32 Combine like terms: 14 + -32 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 7(5)+5(10)=85 | | x+27=4x+9 | | 7(5)+5(10)=0 | | -2x-10=2x+22 | | 40=40 | | 7x+5y=85 | | 2r+3=21pi | | (2x-1)+(3x+7)=16 | | -72n=6624 | | -12/17= | | 24x-4x^2=32 | | -3/5×4/1 | | (y-15)/3= | | -3/5×4 | | 50/x | | (y-15)/3=-12/17 | | -2/3x-18=-6 | | (y-15)/13=-12/17 | | 1/3x.39= | | 3/4=9/16 | | 1/3x0.39= | | 8(y-3)=-40 | | 3x+x-7=25 | | 5(y-4)+11=2y+30 | | 9ln(2x)=81 | | -3(3x-2)+5(x-3)=2x+5 | | (8x+7)(8x^2+5x+4)= | | -3w-6=3(w-4) | | 6y+5s=-12 | | 7y+3=9y+13 | | (x)+(5X)+(x-2)=61 | | x+(5X)+(x-2)=61 |